Recent Ethnographic Research - Upper Churchill River Drainage, Saskatchewan, Canada - Jarvenpa, Robert (ARCTIC, 1979)
Recent developments in ethnographic research in the Upper Churchill River drainage of northwestern Saskatchewan are reviewed. These include an analysis of the spatial organization of trapping economics, and an examination of behavioral responses to current technological impact (particularly housing, imported food and machinery, and new roads) in a southern Chipewyan community. Although high-income trappers generally exploit the largest trapping areas at the greatest distances from a primary settlement, the increasing congregation of short-distance trappers near the village may be exacerbating ecological and economic instability associated with new consumer goods and purchasing habits. Another direction of research involves analysis of economic and social interactions between Chipewyan and Cree communities that shed light upon processes of inter-tribal communication, symbiosis, enmity and identity management.